Comparison of emissions of gaseous and particulate pollutants from the combustion of biomass and coal in modern and old-type boilers used for residential heating in the Czech Republic, Central Europe - Křůmal, Kamil; Mikuška, Pavel; Horák, Jiří; Hopan, František; Krpec, Kamil (Chemosphere, 2019)
The chemical composition of emissions from old-type (an overfire boiler, a boiler with down-draft combustion) and modern-type (an automatic and a gasification boiler) boilers was compared. The boilers were operated with different fuels (brown and hard coal, wet and dry wood, wood pellets and brown coal briquettes) with reduced output (40-60%). The emissions were characterized by the contents of gaseous components (NOx, SO2, CO, CO2, OGC); and particulate organic compounds (alkanes, polycyclic aromatic hydrocarbons, saccharides), including organic markers (monosaccharide anhydrides, diterpenoids, methoxyphenols, hopanes), which are used for source apportionment of particulate matter in ambient air. In general, emissions of the products of incomplete combustion (CO, particles, polycyclic aromatic hydrocarbons) were higher from the combustion of solid fuels in old-type boilers than from that in modern-type boilers. The modern-type (especially automatic) boilers were the most environmentally friendly. The highest concentrations of particulate matter (81.6-89.4 g kg-1) and particulate organic compounds (sum of PAHs: 225-275 mg kg-1) including organic markers were found in emissions from old-type (overfire) boilers, especially with the combustion of brown and hard coal. Characteristic ratios of selected organic compounds/markers applied for source identification were calculated. Computed characteristic ratios for monosaccharide anhydrides (biomass combustion) agreed with values in the literature. Homohopane indexes, frequently used for identification of coal combustion, and other characteristic ratios for PAHs, were different from the literature data. In our opinion, characteristic ratios for PAHs are not suitable for use in source apportionment.
Keywords: Levoglucosan; Europe; Reduced output; uhlí; Biomass; vytápění; Heating; Household heating; Hopanes; Coal; Evropa; plyny; Polycyclic aromatic hydrocarbons; Czech Republic; polycyklické aromatické uhlovodíky; Polycyclic Aromatic Hydrocarbons; Česká republika; Gases; biomasa